[Cu]-Catalyzed S(N)AR reactions: direct amination of electron deficient aryl halides with sodium azide and the synthesis of arylthioethers under Cu(II)-ascorbate redox system - Goriya, Yogesh; Ramana, C. V. (Tetrahedron, 2010)
A one pot [Cu]-promoted SNAr reaction of electron-deficient halobenzenes with sodium azide and the reduction of the intermediate aryl azides under the same Cu(II) ascorbate redox conditions leading to anilines has been documented. Control experiments revealed that both ascorbate and proline play important role in the reaction path way. Further, the use of this catalytic Cu(II) ascorbate redox system has been explored for the synthesis of arylthioethers. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Anilines; Azide reduction; Cu(II)-ascorbate redox system; SNAr reaction; Thioether

Ruthenium-catalyzed C6-propenylation reactions of substituted pyridine derivatives: directed and direct C-H activation - Goriya, Yogesh; Ramana, Chepuri V. (Chemistry-A European Journal, 2012)
Keywords: alkenylation; C?H activation; nitrogen heterocycles; pyridine derivatives; ruthenium

Evaluation of viability of halogen•••O2N interactions: insight form crystal packing in a series of isomeric halo and nitro substituted triaryl compounds with modular positioning of halogen and NO2 groups - Ramana, Chepuri V.; Goriya, Yogesh; Durugkar, Kulbhushan A.; Chatterjee, Soumitra; Krishnaswamy, Shobhana; Gonnade, Rajesh G. (CrystEngComm, 2013)
A series of isomeric triaryl compounds with a modular positioning of the halogen and NO2 groups have been synthesized by the azide–alkyne “click reaction” and have been characterized by single crystal X-ray structure analysis. This isomeric series has provided an opportunity for understanding the efficiency of the bifurcated halogen⋯NO2 synthon in the organization of the molecules in the crystalline lattice. The changes in molecular conformation, crystal packing and supramolecular aggregation due to the change in the relative positioning of the complementary groups, halogen atom and the NO2 group on ring A and ring C respectively, have been discussed. All the isomers synthesized are crystalline and establish the triazole as a reliable linker for crystal engineering oriented molecular synthesis. The 2-NO2 derivatives display in general, a helical architecture and 3-NO2 derivatives exhibit a centrosymmetric dimeric assembly via the complementary C–H⋯O interactions leading to either a helical or a 2-dimensional sheet pattern. The molecular organization in 4-NO2 derivatives revealed in general a 2D sheet pattern.

Synthesis of pseudo-indoxyl derivatives via sequential Cu-catalyzed SNAr and Smalley cyclization - Goriya, Yogesh; Ramana, Chepuri V. (Chemical Communications, 2013)
ortho-Bromophenyl sec-alkyl/sec-alkenyl ketones, on reaction with sodium azide in the presence of copper salts, undergo sequential SNAr followed by Smalley cyclization to provide pseudo-indoxyl derivatives. Some of these pseudo-indoxyl derivatives exhibit interesting fluorescent properties and broad Stokes shifts.

2-Aroylindoles from o-bromochalcones via Cu(I)-catalyzed SNAr with an azide and intramolecular nitrene C-H insertion - Goriya, Yogesh; Ramana, Chepuri V. (Chemical Communications, 2014)
A simple procedure for the synthesis of 2-aroylindole derivatives comprising a one-pot CuI-catalyzed SNAr reaction of o-bromochalconeswith sodium azide and subsequent intramolecular cyclization through nitrene C-H insertion has been developed. This protocol is also applicablewith the 2'-bromocinnamates giving the indole-2-carboxylates.